COLLES FRACTURE – HISTORICAL RETROSPECTION - Erčić, Jadran (Srpski medicinski časopis Lekarske komore, 2025)
The author presents a short historical retrospection of the most important surgeons who studied Colles fracture, in chronological order. The author also describes the eponyms most commonly used in daily surgical practice, along with the historical figures that they are linked to.